Exploring Extracurricular Activities in Bangladesh: Access, Gender Disparities, and Shifts in Online Engagement - Jubair, Hassan; Mehenaz, Mithela (Penerbit Hellow Pustaka, 2025)
This study investigates the accessibility, gender disparities, and preferences related to extracurricular activities (ECAs) among students in Bangladesh. Utilizing a survey conducted with middle school, high school, and undergraduate students, we explore the challenges faced by urban versus rural students, the specific barriers encountered by female students, and the preferences for online versus offline ECAs. The results reveal significant disparities, with rural students and female participants facing considerable obstacles in accessing ECA opportunities. A strong preference for online ECAs is evident, although awareness of existing platforms facilitating ECA opportunities is limited. The findings highlight the need for targeted interventions to improve ECA accessibility, promote gender equality, and enhance the visibility of ECA resources. This study provides actionable recommendations to foster a more inclusive environment for ECA participation, ultimately contributing to the holistic development of students across Bangladesh.